ECONOMIC EMPOWERMENT OF VILLAGE COMMUNITIES THROUGH FINANCIAL MANAGEMENT TRAINING AND SUSTAINABLE MICRO-BUSINESS DEVELOPMENT IN LHOKSEUMAWE CITY - Sutan Febriansyah; Muhammad Multazam; Almunadiya; Raudhatinur; Nura Usrina; Yusnidar; Lia Rista (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
This activity aims to increase the financial literacy capacity of village communities, strengthen the ability of micro-entrepreneurs to manage business finances effectively, and encourage the sustainability of businesses based on local potential. The training was held for one day and attended by 35 participants consisting of MSMEs, entrepreneurial housewives, and village youth in the Lhokseumawe City area. The implementation method included three main stages, namely: (1) preparation and coordination with village partners; (2) implementation of the training covering two main materials—simple financial management and sustainable micro-enterprise development strategies; and (3) evaluation and mentoring after the training for two months. A participatory approach was used so that participants actively discussed and directly implemented financial recording practices. The results of the activity showed a significant increase in participant understanding and skills. Before the training, only around 28% of participants were able to record their finances, while after the training, this figure increased to 87%. Participants also showed increased awareness of the importance of separating personal and business finances, and began planning more targeted business development strategies. In addition, small business groups were formed at the village level as an initial step towards sustainable economic empowerment. This PKM activity makes a real contribution to increasing the economic capacity of village communities and strengthening collaboration between universities and the community.